The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3758/s13415-011-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

“Wanted!” The effects of reward on face recognition: electrophysiological correlates

Abstract: The aim of the present study was to uncover the temporal dynamics of face recognition as a function of reward. Event-related potentials (ERPs) were recorded during the encoding and the subsequent old/new memory test in response to faces that could be associated with a monetary reward. The behavioral results showed that faces associated with reward at both encoding and retrieval were recognized better than the unrewarded ones. ERP responses highlighted that successful encoding predictive of subsequent memory wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 96 publications
(123 reference statements)
4
32
2
Order By: Relevance
“…Unexpectedly, however, this effect was limited to faces and did not extend to scene stimuli. While previous studies on similar tasks have used either faces (Marini et al, 2011) or scenes (Bunzeck et al, 2009) our results seem to suggest that when being used within one experimental session reward can have selective effects on reaction-times. This might, for instance, relate to differences in the biological significance of both stimulus categories (Park et al, 2010) and remains to be further explored.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Unexpectedly, however, this effect was limited to faces and did not extend to scene stimuli. While previous studies on similar tasks have used either faces (Marini et al, 2011) or scenes (Bunzeck et al, 2009) our results seem to suggest that when being used within one experimental session reward can have selective effects on reaction-times. This might, for instance, relate to differences in the biological significance of both stimulus categories (Park et al, 2010) and remains to be further explored.…”
Section: Discussioncontrasting
confidence: 43%
“…4D). Indeed, earlier EEG studies on the link between reward and declarative memory have found similar response patterns (Gruber and Otten, 2010;Marini et al, 2011) and they suggest that neural activity over prefrontal sensors plays a critical role for improved learning by reward.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…With respect to the target, this enhanced N2 also indicates that participants were able to rapidly boost early processing of relevant information if they are cued with reward information. The early occipital brain activity was again paired with a frontal positivity and was followed by a notably more frontal P3 wave, perhaps a P3a like component (Luck, 2004; Luck & Kappenman, 2011; Polich, 2007), which would appear to reflect the reward-related boosting to improve processing of the target (Krebs et al, 2013; Goldstein et al, 2006; Marini, Marzi & Viggiano, 2011; Wu & Zhou, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The incentive role of reward and its effects on behavior can be achieved through modulations of attentional and cognitive control. These modulations include enhancing attentional preparation under conditions of reward prospect (Van den Berg et al, 2014), enhanced recruitment of cognitive resources (Krebs, Boehler, Roberts, Song, & Woldorff, 2012; Vassena, Silvetti, Boehler, Achten, Fias et al, 2014), reduction of conflict (Padmala & Pessoa, 2011; Krebs, Boehler, & Woldorff, 2010), stopping-induced stimulus devaluation (Wessel, O'Doherty, Berkebile, Linderman & Aron, 2014), reactive response inhibition (Boehler, Schevernels, Hopf, Stoppel, & Krebs, 2014), and optimized memory encoding (Marini, Marzi, & Viggiano, 2011). Moreover, the Eriksen flanker task in association with monetary rewards has been already used in previous studies of selective attention (Seifert et al 2006; Hubner & Schlosser, 2010), cognitive control (Braem, Hickey, Duthoo & Notebaert, 2014) and conflict adaptation (van Steenbergen, Band & Hommel, 2009; Braem, Vertguts, Roggeman & Notebaert, 2012), suggesting the usefulness of this paradigm for the goals of the present study.…”
Section: Introductionmentioning
confidence: 99%